Bioconversion of white sorghum biomass using MixAlco fermentation process - Fawzia Shalsh (Dysona. Applied Science, 2021)
Agricultural waste is a major environmental challenge, especially in developing countries. Lignocellulose biomass is a low-cost bioresource with great potential for bioethanol and bioproducts production. However, the high costs of the enzymic treatment restrict agricultural mass utilization. MixAlco process applied methane-inhibited route to convert environmental waste into carboxylate salts under non-sterile anaerobic fermentation conditions. In this study, the lime-treated agricultural residue of white sorghum biomass (80%) supplemented by chicken manure (20%) was fermented under anaerobic conditions in a stirred-tank bioreactor. The fermentation process resulted in an acid concentration of 21.03 g/L at a conversion rate of 54.4 % for the initial volatile solids. The fermentation products constituted mainly of acetic acid, followed by propanoic acid and ethanol. The current research indicates that the MixAlco biotechnology that uses mixed agricultural wastes as a fermentation material provides an economical substitute to chemicals and physical processing methods.